Mapping Global Research on Infection Prevention and Control for Patient Safety: A Scopus, and VOSviewer Based Bibliometric Analysis (2019–2024) - Miry, Abdullah; Ulfa, Maria (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Infection prevention and control (IPC) have a significant impact on patient safety and healthcare quality, particularly in global health catastrophes such as the COVID-19 pandemic. The study aims to examine global research trends in infection prevention and control (IPC) and patient safety between 2019 and 2024. In addition to providing insight into the development and direction of IPC research, it highlights significant authors, issue fields, and notable works. Methods: A bibliometric analysis was conducted using the Scopus database, encompassing a total of 180 documents as of April 1, 2025. The inclusion criteria were documented type ‘Articles’ and ‘reviews’ subject area ‘medicine’ and ‘nursing’ language ‘English’ from 2019- 2024. Data were analysed using Scopus, VOSviewer version 1.1.20. Results: The COVID-19 pandemic led to a significant increase in IPC research, culminating in the highest output in 2024. The United States and the United Kingdom were major contributors, while Switzerland, India, South Africa, and Australia showed strong regional participation. Notably, rising contributions from low- and middle-income countries (LMICs) signal growing global inclusivity. Mainly, institutional contributors included the World Health Organisation (WHO) and Hôpitaux Universitaires de Genève. D. Pittet was recognised as the most productive author. Citation analysis identified highly influential studies, with the top-cited article being 129 citations. Keyword co-occurrence mapping revealed nine thematic clusters, including infection control practices, personal protective equipment, and healthcare quality improvement. Conclusion: As demonstrated by the growing research output and global collaboration, the findings reflect the evolution of IPC into a multidisciplinary domain, exposing underexplored regions and themes in the literature. IPC has emerged as a central pillar of Contemporary health systems. Rising contributions from low— and middle-income countries indicate increased global engagement and adherence to international standards.